Nasal carriage, microbial resistance and genetic characterization of Staphylococcus aureus in cows in Turkey - Abughonem, H; Halac, B; Kekec, AI; Maslak, B; Bağcigil, AF (Journal of the Hellenic Veterinary Medical Society, 2024)
The aim of this study is to determine the isolation rates of S. aureus from nasal swabs of healthy cattle, antibiotic resistance profiles of isolates and to investigate the resistance genes associated with antibiotic resistance. For this purpose; 250 nasal swab samples collected from healthy dairy cattle in farms located in four different provinces (Istanbul, Bursa, Kırklareli and Tekirdağ) examined for S. aureus. S.aureus was isolated from 7.6% (n=19) of the examined cows. Antibiotic susceptibility of isolates was determined by disc diffusion method. The isolates were resistant to penicillin (78.95%); tetracycline (68.42%); erythromycin (63.16%); doxycycline (36.84%); cefaperazone (31.58%); cefoxitin (26.32%); ceftiofur (26.32%) and clindamycin (21.05%), while all were sensitive to penicillin-novobiocin, linezolid, quinupristin-dalfopristin, chloramphenicol, gentamicin, trimethoprim-sulphametoxazole and enrofloxacin. It was determined that 5 of 12 isolates resistant to erythromycin had inducible clindamycin resistance. Antibiotic resistance genes and pvl gene were examined by Polymerase Chain Reaction method. The most common genes detected in the isolates were blaZ (93,33%), mecA (52.63%), tetL (23,08%), tetK (53,85%), ermB (8,33%) and ermC (41,67%). ermA, tetM, tetO and pvl genes were not detected in any of the isolates. In our study, the most common type of SCCmec was found to be type IV 90% (n=9) and only one isolate type I 10% (n=1).